PENGARUH EARNING PER SHARE (EPS), PRICE EARNING RATIO (PER) PRICE TO BOOK VALUE (PBV) DAN NET PROFIT MARGIN (NPM)TERHADAP DEVIDEN PAYOUT RATIO (DPR) - Dheri Febiyani Lestari (JEKP (Jurnal Ekonomi dan Keuangan Publik), 2022)
AbstractThe purpose of this study to know and analyze the Influence Earning Per Share (EPS), Price Earning Ratio (PER), Price to Book Value (PBV) and Net Profit Margin (NPM) of the Dividend Payout Ratio (DPR) at a manufacturing company in Indonesia Stock Exchange year period 2012-2014 partial and simultaneous. The method used by the author was the correlation method, the technique of data collection was done by used secondary data such as financial statements manufacturing company in Indonesia Stock Exchange 2012-1014 period. The sample in this study manufacturing company in Indonesia Stock Exchange 2012-1014 period by 22 companies. In this study, the analysis used was multiple regression analysis. The results of data analysis showed EPS and PER negatively affect, PBV and DPR NPM significant effect on EPS DPR, and PBV PER NPM significant effect on the Parliament on Manufacturing Company in Indonesia Stock Exchange year period 2012-2014Keywords: Earning Per Share (EPS), Price Earning Ration (PER), Price to Book Value (PBV), Net Profit Margin (NPM Dividend Payout Ratio(DPR) AbstrakPenelitian ini bertujuan untuk mengetahui dan menganalisis Pengaruh Earning Per Share (EPS), Price Earning Ratio (PER), Price to Book Value (PBV) dan Net Profit Margin (NPM) terhadap Deviden Payout Ratio (DPR) pada perusahaan manufaktur di Bursa Efek Indonesia periode tahun 2012-2014 secara parsial dan simultan Metode penelitian yang digunakan oleh penulis adalah deskriptif verifikatif, dengan teknik pengumpulan data dilakukan dengan menggunakan data sekunder berupa laporan keuangan perusahaan manufaktur yang terdaptar di Bursa Efek Indonesia periode 2012-2014. Sampel dalam penelitian ini perusahaan manufaktur yang terdaptar di Bursa Efek Indonesia periode 2012-2014 sebanyak 22 perusahaan. Dalam penelitian ini, analisis yang digunakan adalah analisis regresi berganda. Hasil analisis ata menunjukkan EPS dan PER berpengaruh negatif terhadap DPR dan PBV dan NPM berpengaruh signifikan terhadap DPR. EPS, PER PBV dan NPM berpengaruh signifikan terhadap DPR pada Perusahaan Manufaktur di Bursa Efek Indoensia periode tahun 2012-2014Kata kunci : Earning Per Share (EPS), Price Earning Ration (PER), Price to Book Value (PBV), Net Profit Margin (NPM) Dividend Payout Ratio(DPR)